An Analysis of Politeness Strategy in Pitch Perfect 2 Movie - Helena Dewi Irawansari; Ni Nyoman Deni Ariyaningsih (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2024)
The politeness strategy is a phenomenon of language that is based on the form and purpose of each of them. Politeness strategies are used to convey communication with meaning and purpose to be conveyed and interpreted properly.This study aimed to identify and analyze the politeness strategy used in the Pitch Perfect 2 Movie script. This study used a qualitative descriptive approach in research. And the movie script of Pitch Perfect 2 movie is used as a data source in this research. The theory in this research used by Brown and Levinson about the types of politeness strategies. The data politeness strategies were found in the movie script which were four main strategies: Positive Politeness, Negative Politeness, Bald on Record, and Off-the Record.